2018
DOI: 10.1186/s12944-018-0768-7
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia prevalence, awareness, treatment, control, and risk factors in Chinese rural population: the Henan rural cohort study

Abstract: BackgroundThe prevalence of dyslipidemia continue to increase in recent decades in China, however, little is known about the recent prevalence, awareness, treatment, control, and potential risk factors of dyslipidemia in the rural areas of China.MethodsA total of 39,207 participants aged 18–79 years were recruited for the epidemiological research from the Henan Rural Cohort study. The age- and sex-adjusted means (95% confidence intervals, CI) of serum lipid levels or percentages of prevalence, awareness, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
55
5
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 16 publications
(27 reference statements)
19
55
5
6
Order By: Relevance
“…28 However, many reverse results have been reported between older ages and dyslipidemia control. 7,22,29 Again, differing from our ndings, a positive association between aging and the control of chronic diseases such as hypertension has been reported. 30 Our results may support the nding that dyslipidemias such as raised TC control rates may differ depending on the participants and country, and rates may range from 18-100%.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…28 However, many reverse results have been reported between older ages and dyslipidemia control. 7,22,29 Again, differing from our ndings, a positive association between aging and the control of chronic diseases such as hypertension has been reported. 30 Our results may support the nding that dyslipidemias such as raised TC control rates may differ depending on the participants and country, and rates may range from 18-100%.…”
Section: Discussioncontrasting
confidence: 99%
“…30 Our results may support the nding that dyslipidemias such as raised TC control rates may differ depending on the participants and country, and rates may range from 18-100%. 31 Consistent with prior reports, 22,29 we showed that women were more likely than men to have dyslipidemia awareness, treatment and control. Similarly, two studies on the management of raised LDL-C indicated that women recorded higher likelihood of awareness, treatment and control.…”
Section: Discussionsupporting
confidence: 90%
“…We identified several factors that were associated with dyslipidemia in our study population. Our results that smoking, obesity, central obesity, hypertension, and diabetes can elevate the risk of dyslipidemia has been confirmed in many previous studies [29,30] . We also found that current drinkers had a lower risk of dyslipidemia; a similar result was reported by Song [31] .…”
Section: Discussionsupporting
confidence: 90%
“…The participants of this study were from Henan Rural Cohort study . After excluding participants who received sex steroids or other androgen‐related drugs, 925 individuals aged 18 to 79 with T2DM were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the general characteristics of participants' demography (age, gender, educational attainment, socioeconomic status, etc. ), lifestyles (smoking status, alcohol intake, physical activity), and family history of disease was obtained by well‐trained investigators through face‐to‐face interviews using a structured questionnaire as previously described . The education attainment was categorized into never attended school, primary school, and junior secondary and above.…”
Section: Methodsmentioning
confidence: 99%